Energy and exergy analysis of a heat storage tank with a novel eutectic phase change material layer of a solar heater system - Gurturk, Mert; Koca, Ahmet; Otztop, Hakan F.; Varol, Yasin; Sekerci, Mehmet (Taylor & Francis Inc, 2017)
Solar energy is one of the most important renewable energy sources, but it is not available every time and every season. Thus, storing of solar energy is important. One of the popular methods of heat storage is use of phase change materials (PCMs) which have large thermal energy storage capacity. In this study, the heat storage tank in a domestic solar water heating system was chosen as control volume. The experiments were performed in the province of Elazg, Turkey, in November when solar radiation was weak due to cloudy sky. The heat storage tank of the system was modified to fill PCM between insulation and hot water part. A few PCMs which are Potassium Fluoride, Lithium Metaborate Dihydrate, Strontium Hydroxide Octahydrate, Barium Hydroxide Octahydrate, Aluminum Ammonium Sulfate, and Sodium Hydrogen Phosphate were analyzed to proper operating conditions using a Differential Scanning Calorimeter (DSC) and the best PCM was obtained with the Aluminum Ammonium Sulfate and Sodium Hydrogen Phosphate mixture. Thus, eutectic PCM was obtained and used in a heat storage tank of the solar water heating system. Energy and exergy analysis of heat storage tank was performed with and without the PCM. Energy and exergy analysis has shown that the heat storage tank with the PCM is more efficient than without the PCM and the maximum exergy efficiency was obtained as 22% with the heat storage tank with the PCM.
Keywords: Exergy analysis; phase change material; thermal energy storage unit